A study of factors that influence customer satisfaction in Islamic banking / Nurhafiza Hizam - Hizam, Nurhafiza (Faculty of Business and Management, 2015)
This study was conducted to investigate the customer satisfaction in Islamic Banking among Petronas Carigali Sdn.Bhd. Three (3) independent variables had been identified which are quality of service, behavior of the bank staff and bank image and reputation. 100 respondents had participated in this study. The objectives of this study are to investigate the factors influencing customer satisfaction in Islamic Banking and to examine the most significance factor influencing customer satisfaction in Islamic Banking. To ensure the objective, researchers has use SPSS version 20. The result indicates that the significant variables that influence customer satisfaction in Islamic banking are quality of service, behavior of the bank staff and bank image and reputation. Besides, behavior of the bank staff becomes the best predictor in influence customer satisfaction in Islamic banking.